Young people on social media in a globalized world: self-optimization in highly competitive and achievement-oriented forms of life - Butler, Stephen (Frontiers in Psychology, 2024)
Research investigating young people’s social media use has been criticized for its limited theoretical foundations and scope. This paper elaborates young people’s social media activity from a socio-ecological evolutionary perspective (SEE), where young people’s online exchanges cannot be divorced from the highly competitive and achievement-oriented modern market cultures in which they live. In highly competitive and achievement-oriented forms of life, young people’s social media environments are often constituted as dynamic and evolving extrinsically oriented ecological niches that afford for status and identity enhancement while also affording for peer approval, belongingness, and self-worth nested within, and subordinate to, these higher-order affordances. The extrinsic value organization of social media platforms that serve young people’s status and identity-enhancement are embodied by a community of mutually interdependent criteria that are evolutionary-based, developmentally salient, and market-driven: physical attractiveness, high (educational and extracurricular) achievements, and material success. Young people’s online signaling of these interdependent extrinsic criteria affords for status-allocation and self-enhancement, where each criteria becomes an arena for social competition and identity formation, enabling young people to build personal and optimal models of social success congruent with their own interests and abilities. Young people’s status and identity enhancing signaling of these extrinsic criteria is moving toward increasingly idealized or perfect embodiments, informed by accelerating, short-term positive feedback processes that benefit from the technological affordances and densely rewarding peer environments instantiated on social media.